Determination of mercury in agroindustrial samples by flow-injection cold vapor atomic absorption spectrometry using ion exchange and reductive elution - Gomes Neto, José A. [UNESP]; Zara, Luís F. [UNESP]; Rocha, Julio C. [UNESP]; Santos, Ademir [UNESP]; Dakuzaku, Carolina S. [UNESP]; Nóbrega, Joaquim A. (Elsevier, 2000)
A flow-injection system with a Chelite-S® cationic resin packed minicolumn is proposed for the determination of trace levels of mercury in agroindustrial samples by cold vapor atomic absorption spectrometry. Improved sensitivity and selectivity are attained since mercuric ions are on-line concentrated whereas other potential interferents are discarded. With on-line reductive elution procedure, concentrated hydrochloric acid could be replaced by 10% w/v SnCl2, in 6 M HCl as eluent. The reversed-intermittent stream either carries the atomic mercury, to the flow cell in the forward direction or removes the residue from reactor/gas liquid separator to a discarding flask in the opposite direction. Concentration and volume of reagent, acidity, flow rates, commutation times and potential interfering species were investigated. For 120 s preconcentration time, the proposed system handles about 25 samples h-1 (50.0 500 ng l-1), consuming about 10 ml sample and 5 mg SnCl2 per determination. The detection limit is 0.8 ng l-1 and the relative standard deviation (RSD) (n = 12) of a 76.7 ng l-1 sample is about 5%. Results are in agreement with certified value of standard materials at 95% confidence level and good recoveries (97-128%) of spiked samples were found. (C) 2000 Elsevier Science B.V.
Keywords: Chelite S resin; CVAAS; FIA; Mercury; Reductive elution; hydrochloric acid; mercury; resin; atomic absorption spectrometry; flow injection analysis; ion exchange